Herb endozoochory by cockatoos: Is 'foliage the fruit'?. (6th November 2019) - Blanco, Guillermo; Bravo, Carolina; Chamorro, Daniel; Lovas‐Kiss, Ádám; Hiraldo, Fernando; Tella, José L.
Abstract: Establishing whether herb seed endozoochory is accidental or has evolved independently or in combination with other dispersal mechanisms may be valuable in the study of plant–animal interactions, but it remains unexplored for birds. We tested whether an Australian cockatoo, the galah ( Eolophus roseicapilla ), swallows entire seeds when feeding on other tissues without subsequent seed digestion, thus enhancing seed dispersal (the 'foliage is the fruit' hypothesis). Our preliminary sampling provides strong evidence supporting that this seed predator also acts as a legitimate endozoochorous disperser. A large proportion of droppings contained numerous seeds of six herb species of three plant families, surviving gut passage to be dispersed as viable propagules. The wide range in the number of seeds found in combinations with up to five species in particular droppings suggests both simultaneous and sequential passive ingestion without seed digestion and/or focused seed predation and digestion. As expected for inadvertent ingestion and inefficient digestion, our findings suggest that seed number and richness of dispersed plants are associated traits in this particular mutualistic interaction. This relationship can have important implications in community‐wide processes, favouring herbs whose seeds are disseminated in a viable state over those predated or negatively affected by gut transit. Abstract :